Temozolomide analog PMX 465 downregulates MGMT expression in HCT116 colorectal carcinoma cells - Yang, Zhikuan; Wei, Danping; Liu, Feifei; Liu, Jing; Wu, Xiaoming; Stevens, Malcolm F. G.; Bradshaw, Tracey D.; Luo, Ying; Zhang, Jihong (Wiley, 2018)
The efficacy of temozolomide (TMZ) treatment for cancers is currently limited by inherent or the development of resistance, particularly, but not exclusively, due to the expression of the DNA repair enzyme O6-methylguanine-DNA methyltransferase (MGMT) in a significant proportion of tumours. We have found that TMZ analogue C8-methyl imidazole tetrazine (PMX 465) displayed good anticancer activity against the colorectal carcinoma HCT116 cells which are MGMT-overexpressing and mismatch repair (MMR)-deficient. In this study, we found that PMX 465 could downregulate the expression of MGMT in HCT116 cells at the protein and mRNA levels. We found that PMX 465 could reduce MGMT expression by increasing the binding of wild-type p53 to the MGMT promoter and reducing the binding of Sp1 to the MGMT promoter.